Assessment Indicator System for Market Connectivity of the Hainan Free Trade Port in China - Wang, Ziyun; Li, Zhe (Asia Pacific Economic and Management Review, 2026)
On December 18, 2025, the Hainan Free Trade Port in China officially commenced its island-wide customs closure operation. This marks the practical implementation of its institutional framework characterized by front-line liberalization, second-line management, and on-island freedom. This paper provides an operational definition of market penetration and establishes two subsystems: a facilitation penetration subsystem (U1) and a risk prevention and control subsystem (U2). In terms of index design, a three-tier indicator system is constructed. U1 primarily evaluates the level of penetration, incorporating indicators such as customs clearance efficiency, reduction of institutional costs, and second-line traffic flow. U2 mainly assesses risk controllability, including indicators like tax compliance, risk early warning, and emergency response. Methodologically, the indicators are first standardized. Then, the weights for the two subsystems are determined using the entropy weight method and combined weighting. Subsequently, this paper introduces a coupling coordination degree model to develop a controllable openness coordination index. This index addresses a core research question: as the level of facilitation improves, whether risk prevention and control capabilities can keep pace and whether synergistic effects are achieved. This study translates key systemic requirements for customs closure operations into observable and quantifiable indicators, thereby creating a set of reproducible evaluation tools. These tools can be applied for operational assessment in the first year of customs closure, stress testing, system refinement, and ultimately, for developing a sustainable and updatable policy dashboard.